(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
Although Philip Larkin and Edward Hopper, an English poet and an American painter, worked in two different domains of art and different cultural contexts, their works evoke similar emotions and comments among the public. The recipients regularly mention three major themes of Larkin’s poems and Hopper’s paintings, which are loneliness, sadness and irony. This article aims to discuss how the poet represented them in words and the painter on canvas. I will study the individual style of both artists in order to reveal how various aspects of their works correspond with each other, leading to similar artistic effects.